PENGARUH MEDIA ANIMASI BERBASIS AUDIO-VISUAL DALAM PEMBELAJARAN E-LEARNING TERHADAP HASIL BELAJAR KELAS III SD - Kristiandar, Fadilah Yulia; Kamidjan, Kamidjan; Wiyadi, Heru (IJPSE : Indonesian Journal of Primary Science Education, 2020)
The purpose of this research were to determine the result of the influence of Audio-visual-based animation media on learning the students of the third grade Elementary School on a 7 subthemes learning energy source 1. This type of research uses pre-experimental research subject in the third grade SDN Kepanjen 1 Jombang for experimental class. Data collecting technique uses observation, documentation and tests. The results of data analysis techniques show that by using audio-visual based animation media the learning process is more meaningful and students do not feel bored. Animation is a moving picture accompanied by sound, arranged in orderly manner following the set of motion at each additional count of time. The audio-visual-based animation is made through the powtoon applications. from the pretest and posttest they got the average score of pretest was 67.88 and posttest was 81.92. it can be concluded that there was a positive influence on the use of audiovisual- based animation media on learning of a 7 subthemes learning energy source 1.